The Influence of Social Media Use, E-Commerce, and Korean Wave on The Entrepreneurial Interest of Dharma Andalas University Students - Putri, Loli Amanda; Chairoel, Lucy (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Unemployment remains a persistent issue that could be mitigated through entrepreneurship. One cause was the lack of interest in and awareness of entrepreneurship among students.Purpose: This study's objective is to assess the impacts of social media usage, E-commerce, and the Korean wave on the entrepreneurial interest of students at Dharma Andalas UniversityDesign/methodology/approach: A quantitative approach was employed with a sample of 133 students from the University of Dharma Andalas. Data were gathered through online questionnaires and analyzed using multiple linear regression in SPSS.Findings/Results: The research outcomes reveal that (1) the use of social media has a positive and significant effect on the entrepreneurial interest of students at Dharma Andalas University; (2) e-commerce has a positive and significant effect on the entrepreneurial interest of students at Dharma Andalas University; (3) the Korean wave has a positive and significant effect on the entrepreneurial interest of students at Dharma Andalas University; and (4) the use of social media, E-commerce, and  Korean wave has a positive and significant effect on the entrepreneurial interest of students at Dharma Andalas University.Conclusion: Students are encouraged to leverage social media, E-commerce, and the Korean wave for entrepreneurial opportunities, with universities supporting them through training and offering business incubators.  Originality/value: This study offers a novel contribution by highlighting the importance of the Korean Wave in entrepreneurship. Keywords: social media, e-commerce, Korean wave, business, entrepreneurial interest